Quadri-Chamber Thrombi and Impending Paradoxical Embolism - Samier Deen, DO; Paul Gilbert, MD; Kush Agrawal, MD; Abby Borhan, MD (JACC: Case Reports, 2024)
Thrombus-in-transit through patent foramen ovale (PFO) is an extremely rare diagnosis that can often be associated with pulmonary embolism. Currently, data exists to guide management options; however, there is no medical consensus with regard to the optimal treatment strategy for thrombus-in-transit through PFO.